Analysis of E-Module Containing Culturally Responsive Teaching to Improve Pancasila Education Learning Outcomes of Elementary School Students - Zimmy P. Siringo-Ringo; Ellianawati Ellianawati; Bambang Subali; Woro Sumarni; Rhodentia Sri Hastuti Tamba (JURNAL ASIMILASI PENDIDIKAN, 2026)
This research aimed to analyze the effectiveness of an e-module based on Culturally Responsive Teaching (CRT) in improving learning outcomes for elementary school students in Pancasila Education. The research is motivated by the need for more contextual, meaningful, and culturally relevant learning approaches that align with students’ backgrounds and experiences. This research used the Systematic Literature Review (SLR) method with the SALSA framework and PRISMA guidelines to ensure a systematic and transparent article selection process. The analyzed articles were published between 2021 and 2026 and were relevant to the research topic. The study results indicate that an electronic module-based CRT can improve students' learning outcomes and engagement. The integration of local cultural values in digital teaching materials helps students understand the material more contextually and meaningfully. Thus, an electronic module-based CRT is an effective learning innovation in improving the quality of Pancasila Education learning in elementary schools.